Comparative study of the chemical additives Consolid 444 and Con-Aid for the improvement of the subgrade in clay soils (Gaceta Técnica, 2023)
The goal of this investigation was to compare the chemical additives Consolid 444 and Con-Aid to improve the bearing capacity of a clayey soil. The samples were taken from the section of the Pedro Ruiz - San Carlos highway between km 3+000 and 4+000, province of Bongará, Peru; likewise, laboratory tests were carried out to determine the physical and mechanical properties of the stabilized and unstabilized soil. The results obtained indicated that the natural soil was classified as CL according to SUCS, and AASHTO as A-7-6 (17), in addition with the addition of 0,035% for the Consolid 444 additive and 2 ml for the Con-Aid additive, an increase in CBR was achieved at 95% from 5.49% to 28,65% and 24,32% respectively. On the other hand, it was verified that the CBR value increased, by increasing the curing periods at 7, 14 and 28 days for both additives. In conclusion, the Consolid 444 and Con-Aid additives improved the mechanical behavior of clayey soil
Keywords: subgrade; clay soils; CBR; Consolid 444; Con-Aid